The Impact of Foreign Aid Conditionality on Poverty Alleviation in Bangladesh: A Recipient’s Perspective - Mamun, Mehadi (Business and Economic Research, 2021)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Donors provide aid to the recipient government with conditions to implement some policies so that the recipient government can use aid effectively and able to improve its economic, social, and political situation as well as reduce its poverty. However, concerns have been raised that aid conditionality has promoted reforms that could not reduce the poverty situation in some countries such as sub-Saharan Africa, while some countries in East Asia were able to break out of poverty and find themselves better off than before the conditional aid was accepted. Hence, the purpose of this study is to examine the impact of foreign aid conditionality on poverty alleviation in Bangladesh. The paper is qualitative in nature and a case study on Bangladesh. The study has been conducted by using secondary data, like journal articles, research papers, and Bangladesh government and aid donors’ reports. The study finds that Bangladesh has started to show considerable improvement in reducing poverty, though it is still ranking low on the Human Development Index. The findings have important implications for policymakers and captured insights about the foreign aid conditionality in Bangladesh.